Transnational innovation systems for bioeconomy: insights from cassava value chains in East Africa - Lutta, Alphayo I.; Bößner, Stefan; Johnson, Francis X.; Virgin, Ivar; Trujillo, Monica; Osano, Philip (Frontiers in Sustainable Food Systems, 2024)
In this study, we analyze the purpose, challenges, and opportunities of transnational innovation systems using cassava as the case study crop in the East Africa region. Cassava scientifically referred to as Manihot esculenta Crantz, is an important food security crop for the poor and vulnerable and a potential building block for advancing the bioeconomy in Africa and the global South. Semi-structured interviews with researchers, government official, and small and medium enterprise representatives from the region were done to determine their level of collaborations with other partners across the region and the opportunities and challenges for transnational innovation systems along the cassava value chain. The selection of interviewees followed a purposive sampling technique according to their knowledge on transnational innovation in the cassava value chain. This was corroborated by a focused literature review on innovation systems concepts gathered from scholarly literature. The findings show that transnational collaborations and innovations in the East African region offer opportunities for expansion of biomass production, bioprocessing, and value addition to the rich bioresources available. Collaboration across borders and transnational innovation systems were found to play an important role for advancing and/or upscaling cassava breeding, growing, value-adding products and novel processing methods and contributing to a growing East African bioeconomy. Other than the regional policy challenges, organizational and cultural barriers were more prominent in venturing, participation, and involvement of parties and users in transnational innovations. These findings draw attention to the often unnoticed, but vital, role that institutional and policy frameworks play in initiating as well as supporting transnational innovation systems that address issues of current and future global concern. Therefore, appropriate policy environment and partnerships that offer opportunities for synergy and complementarity are vital for building effective transnational innovation systems that enhance the sustainability of production, value addition and end-uses of biobased cassava products.